2010
DOI: 10.1123/pes.22.2.278
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Young Male Swimmers in the 100-Meters Front Crawl

Abstract: Youth swimming performance may be influenced by anthropometric, physiology and technical factors. The present paper examined the role of these factors in performance of 100m freestyle in swimmers 12–14 years of age (n = 24). Multiple regression analysis (forward method) was used to examine the variance of the 100 meters front crawl. Anaerobic power, swimming index and critical speed explained 88% (p < .05) of the variance in the average speed of 100 meters front crawl among young male pubertal swimmers. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 14 publications
1
22
0
1
Order By: Relevance
“…To date, research exploring the development of youth swimmers during adolescence has focussed mainly on male subjects [ 8 , 9 , 10 , 11 ] with comparatively fewer targeting solely young females [ 7 , 12 ]. In one of the few studies on young female swimmers, Lätt, Jürimäe, Haljaste, Cicchella, Purge and Jürimäe [ 7 ] found that development of biomechanical factors such as velocity, stroke length, stroke rate and in particular stroke index, rather than bioenergetics, contributed more to improved performance times in the 400 m freestyle event.…”
Section: Introductionmentioning
confidence: 99%
“…To date, research exploring the development of youth swimmers during adolescence has focussed mainly on male subjects [ 8 , 9 , 10 , 11 ] with comparatively fewer targeting solely young females [ 7 , 12 ]. In one of the few studies on young female swimmers, Lätt, Jürimäe, Haljaste, Cicchella, Purge and Jürimäe [ 7 ] found that development of biomechanical factors such as velocity, stroke length, stroke rate and in particular stroke index, rather than bioenergetics, contributed more to improved performance times in the 400 m freestyle event.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for the lack of further associations between SP and improvements in peripheral and systemic capacity may be related to an improvement in the swim efficiency/movement economy that has previously been shown to differentiate between novice and elite swimmers ( Barbosa et al, 2010 ). An enhanced swim efficiency would be responsible for the improvements in swim velocity, an important determinant of swim performance ( Toussaint, 1990 ; de Mello Vitor & Silveira Böhme, 2010 ). It may be that the acquisition of this improved skill can only be achieved or “learned” via high volume repetitive swim actions and is therefore a key factor in high volume aerobic swim training ( Cunningham & Eynon, 1973 ).…”
Section: Discussionmentioning
confidence: 99%
“…Morais et al, (2016) [14] found a moderate correlation of performance at 100 m front crawl swimming with the arm span of swimmers aged 12-13 years. In another study, Vitor and Bohme (2010) [23] found a high correlation between the 100 m front crawl swimming and age, weight, height, and shoulder width but not between arm span, pelvis width, triceps and subscapular skinfold.…”
Section: Relationship Between Anthropometrics and Performancementioning
confidence: 93%
“…The most often observed relationship between speed and height [7,19,23] can be explained by the fact that the Froude value depends on the height of the swimmer. Higher swimmers have lower Froude values and lower resistance to waves, but the fact is that tall swimmers perform their turn and finish actions with their center of gravity furthest away from the wall, so they swim shorter distance than shorter swimmers [10].…”
Section: Relationship Between Anthropometrics and Performancementioning
confidence: 99%